Intratumoral injection reduces toxicity and antibody-mediated neutralization of immunocytokine in a mouse melanoma model - Zachary S Morris; Paul M Sondel; Amy K Erbe; Jacquelyn A Hank; Alexander L Rakhmilevich; Amber M Bates; Claire C Baniel; Elizabeth G Sumiec; Alexander A Pieper; Anna G Hoefges; Ravi B Patel (Journal for ImmunoTherapy of Cancer)
Background Some patients with cancer treated with anticancer monoclonal antibodies (mAbs) develop antidrug antibodies (ADAs) that recognize and bind the therapeutic antibody. This response may neutralize the therapeutic mAb, interfere with mAb effector function or cause toxicities. We investigated the potential influence of ADA to modify the tumor-binding capability of a tumor-reactive ‘immunocytokine’ (IC), namely, a fusion protein (hu14.18-IL2) consisting of a humanized, tumor-reactive, anti-GD2 mAb genetically linked to interleukin 2. We characterize the role of treatment delivery of IC (intravenous vs intratumoral) on the impact of ADA on therapeutic outcome following IC treatments in an established antimelanoma (MEL) regimen involving radiotherapy (RT) +IC.Methods C57BL/6 mice were injected with human IgG or the hu14.18-IL2 IC to develop a mouse anti-human antibody (MAHA) response (MAHA+). In vitro assays were performed to assess ADA binding to IC using sera from MAHA+ and MAHA− mice. In vivo experiments assessed the levels of IC bound to tumor in MAHA+ and MAHA− mice, and the influence of IC route of delivery on its ability to bind to B78 (GD2+) MEL tumors.Results MAHA is inducible in C57BL/6 mice. In vitro assays show that MAHA is capable of inhibiting the binding of IC to GD2 antigen on B78 cells, resulting in impaired ADCC mediated by IC. When B78-bearing mice are injected intravenously with IC, less IC binds to B78-MEL tumors in MAHA+ mice than in MAHA− mice. In contrast, when IC is injected intratumorally in tumor-bearing mice, the presence of MAHA does not detectibly impact IC binding to the tumor. Combination therapy with RT+IT-IC showed improved tumor regression compared with RT alone in MAHA+ mice. If given intratumorally, IC could be safely readministered in tumor-bearing MAHA+ mice, while intravenous injections of IC in MAHA+ mice caused severe toxicity. Histamine levels were elevated in MAHA+ mice compared with MAHA− mice after reintroduction of IC.Conclusions Intratumoral injection may be a means of overcoming ADA neutralization of therapeutic activity of tumor-reactive mAbs or ICs and may reduce systemic toxicity, which could have significant translational relevance.